The rice SnRK family: biological roles and cell signaling modules - Son, Seungmin; Park, Sang Ryeol (Frontiers in Plant Science, 2023)
Stimulus-activated signaling pathways orchestrate cellular responses to control plant growth and development and mitigate the effects of adverse environmental conditions. During this process, signaling components are modulated by central regulators of various signal transduction pathways. Protein phosphorylation by kinases is one of the most important events transmitting signals downstream, via the posttranslational modification of signaling components. The plant serine and threonine kinase SNF1-related protein kinase (SnRK) family, which is classified into three subgroups, is highly conserved in plants. SnRKs participate in a wide range of signaling pathways and control cellular processes including plant growth and development and responses to abiotic and biotic stress. Recent notable discoveries have increased our understanding of how SnRKs control these various processes in rice (Oryza sativa). In this review, we summarize current knowledge of the roles of SnRK signaling pathways in plant growth, development, and stress responses and discuss recent insights. This review lays the foundation for further studies on SnRK signal transduction and for developing strategies to enhance stress tolerance in plants.